Editorial - Díaz Núñez, Verónica Livier (Centro Universitario de Arte, Arquitectura y Diseño, 2017)
The Journal of Sustainable Housing and Communities is a space for the dissemination of original scientific and technological knowledge on housing, urban development, public policies and sustainable communities, among other related issues, considered complex objects of study , whose processes are part of the city and the territory, so that they can be reinterpreted from different perspectives: from the industrial sector, as a fundamental human right and as an opportunity to contribute to sustainability at the urban level and territorial. With an innovative, plural, experimental and multidisciplinary approach, as well as being part of the editorial strategy of the National Laboratory for Housing and Sustainable Communities CONACYT.